Islam Nusantara sebagai Model Pemikiran dan Pengamalan Islam - Ellyatus Sholihah; Sofyan As-Tsauri; Khoirin Nikmah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islam Nusantara is an Islamic concept that integrates Islamic teachings with the local wisdom of the archipelago, offering a moderate, tolerant, and contextual approach. This concept is rooted in the long history of Islamic acculturation with local culture through peaceful channels, arts, and traditions. As a model of thought, Islam Nusantara emphasises the universality of Islam applied according to the local socio-cultural context, prioritising the values of moderation (wasathiyah), interfaith tolerance, and respect for tradition. In religious praxis, Islam Nusantara includes traditions such as tahlilan, slametan, and the Prophet's maulid, which serve as a means of da'wah and strengthening social solidarity. However, challenges such as globalisation and misunderstanding of the concept require a strategic response to keep Islam Nusantara relevant. As a model of thought and practice, Islam Nusantara reflects the flexibility of Islam in dealing with modern dynamics without losing its principles of universality. With an inclusive approach, Islam Nusantara has the potential to inspire Muslim communities around the world to integrate Islamic teachings with local culture in harmony.